Combined Volt-VAR and Volt-Watt Control for PCC Voltage stabilization in Smart Inverters - Won, Dong Ho; Lee, Kyo Beum (Transactions of the Korean Institute of Electrical Engineers, 2023)
This paper proposes the combined Volt-VAR and Volt-Watt control method of smart inverters to stabilize the point of common coupling (PCC) voltage. The distributed energy sources (DER) using renewable energy such as solar and wind power are increasing because of environmental issues worldwide. When the DER increases, the PCC voltage fluctuates, which causes a decrease in grid stability and power quality. Smart inverter provides grid support function such as Volt-VAR and Volt-Watt control method to eliminate these problems. The Volt-VAR control method adjusts capacitive/inductive reactive power based on the PCC voltage. The Volt-Watt control method stabilizes the PCC voltage by reducing active power. The combined Volt-VAR and Volt-Watt control method reduces the active power while it controls the inductive reactive power to the maximum. This paper proposes the combined Volt-VAR and Volt-Watt control method to improve the stabilization effect of PCC voltage. The effectiveness of proposed method is verified by the simulation and experiment results.
Keywords: Control methods; Coupling voltage; Distributed Energy Resources; Grid-connected; Grid-connected inverte; Point of common coupling; Smart inverters; VAR control; Volt-VAR control; Volt-watt control; Distributed Energy Resource; Grid-Connected Inverter; Smart Inverter; Volt-VAR Control; Volt-Watt Control